2021
DOI: 10.1016/j.xcrm.2021.100407
|View full text |Cite
|
Sign up to set email alerts
|

AdipoAtlas: A reference lipidome for human white adipose tissue

Abstract: Highlights d AdipoAtlas provides a reference lipidome of human white adipose tissue d 1,636 and 737 lipids were identified and quantified by tissue tailored LC-MS lipidomics d AdipoAtlas demonstrates prominent differences between subcutaneous and visceral tissue depots d Obesity leads to the remodeling of sphingo-, ether-, and neutral lipid metabolism

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 71 publications
(110 reference statements)
4
67
0
2
Order By: Relevance
“…The compound annotation has been evaluated using the Kendrick mass defect (KMD) to the CH 2 base [53]. The KMD value of each compound has been plotted versus the specific retention time (Figure S2).…”
Section: Methods Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound annotation has been evaluated using the Kendrick mass defect (KMD) to the CH 2 base [53]. The KMD value of each compound has been plotted versus the specific retention time (Figure S2).…”
Section: Methods Validationmentioning
confidence: 99%
“…To ensure a confident lipid identification, we manually curated lipid annotations by plotting the retention time of a given lipid species against its KMD value to the CH 2 base [53]. The IS mix was used to assess the recovery and to build the calibration curves determining the range of linearity and limit of detection (LOD).…”
Section: Methods Validationmentioning
confidence: 99%
“…These differences likely reflect the metabolic activity and function of each tissue, as phospholipids regulate UCP1 within mitochondrial inner membranes of thermogenic BAT cells, whilst TG species are typically stored in WAT ( Leiria and Tseng, 2020 ). Despite the lower levels of ether lipids in SAT compared to BAT, lipidomic analysis of human WAT reported that plasmalogens are still highly abundant relative to other lipid species ( Lange et al, 2021 ). Findings showed that PE plasmalogens were the most abundant species containing PUFA as well as the fourth most abundant lipid class overall.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…Findings showed that PE plasmalogens were the most abundant species containing PUFA as well as the fourth most abundant lipid class overall. Interestingly, PE plasmalogen levels were around 3 times higher than PE-diacyl species ( Lange et al, 2021 ). Interestingly, another study that conducted lipidomic analysis on primary brown, white and beige adipocytes in vitro revealed contrary results ( Schweizer et al, 2019 ).…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation